Technical design of the phase I Mu3e experiment - Arndt, Kirk; Augustin, Heiko; Baesso, P.; Berger, N.; Berg, F.; Betancourt, C.; Bortoletto, D.; Bravar, A.; Briggl, K.; vom Bruch, D.; Buonaura, A.; Cadoux, F.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
The Mu3e experiment aims to find or exclude the lepton flavour violating decay μ→eee at branching fractions above 10−16. A first phase of the experiment using an existing beamline at the Paul Scherrer Institute (PSI) is designed to reach a single event sensitivity of 2⋅10−15. We present an overview of all aspects of the technical design and expected performance of the phase I Mu3e detector. The high rate of up to 108 muon decays per second and the low momenta of the decay electrons and positrons pose a unique set of challenges, which we tackle using an ultra thin tracking detector based on high-voltage monolithic active pixel sensors combined with scintillating fibres and tiles for precise timing measurements.
Gesehen am 15.02.2022